Role of Inflammatory Cell Subtypes in Heart Failure - Derek Strassheim; Edward C. Dempsey; Evgenia Gerasimovskaya; Kurt Stenmark; Vijaya Karoor (Journal of Immunology Research)
Inflammation is a well-known feature of heart failure. Studies have shown that while some inflammation is required for repair during injury and is protective, prolonged inflammation leads to myocardial remodeling and apoptosis of cardiac myocytes. Various types of immune cells are implicated in myocardial inflammation and include neutrophils, macrophages, eosinophils, mast cells, natural killer cells, T cells, and B cells. Recent clinical trials have targeted inflammatory cascades as therapy for heart failure with limited success. A better understanding of the temporal course of the infiltration of the different immune cells and their contribution to the inflammatory process may improve the success for therapy. This brief review outlines the major cell types involved in heart failure, and some of their actions are summarized in the supplementary figure.